Monetary policy and macroprudential regulation with financial frictions - Agénor, Pierre-Richard (Cambridge, Massachusetts : MIT Press, 2020)
"A monograph that accounts for financial frictions in some of the most-used macroeconomic models. An attempt to bring practical reality into macroeconomic theory"--
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Monetary policy -- Econometric models; Macroeconomics; ECONOMICS/Macroeconomics